Bovine Brucellosis In Reproductive Disorders Of Dairy Animals In Peri-Urban Areas Of Gujarat - Patel, M.D.; Patel, P.R.; Tyagi, K.K.; Sorathiya, L.M. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Bovine brucellosis - a significant zoonotic disease is commonly prevalent in dairy animals worldwide with varying magnitude between herds, locations, states and countries requiring sound surveillance to design proper control measures. A surveillance of brucellosis in reproductive disorders of bovines of peri-urban areas of Gujarat, India was therefore conducted using various diagnostic tests. Total 5036 animals in 199 herds of bovines (cattle-1720 and buffaloes-3316) from peri-urban areas were monitored for occurrence of reproductive disorders. Total 16.90% (849) bovines suffered from various reproductive disorders. Of these reproductive disorders cases, 18.30% (155) were found positive for Brucella abortus antibodies. Among Brucella positive cases of reproductive disorders, significantly (p=0.000) higher prevalence of bovine brucellosis was found in cases of abortion (45.50%) than other reproductive disorders. The prevalence of bovine brucellosis in reproductive disorders of bovine in different peri-urban areas varied non-significantly between 12.60 and 23.90% (p
Keywords: Bovine Brucellosis; Diagnostic Tests; Peri-urban Areas; Reproductive Disorders